2006
DOI: 10.2166/wst.2006.381
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure of activated sludge during aerobic granulation in an annular gap bioreactor

Abstract: A novel annular gap reactor was designed to create a controlled shear environment in which aerobic granular sludge could be developed. The bacterial and eukaryal community structures during two aerobic granular sludge experiments were tracked using denaturing gradient gel electrophoresis (DGGE). The first granule cultivation experiment, using an organic loading rate of 1.6 kg/m3d COD, resulted in biomass that was dominated by filamentous bacteria and Zoogloea ramigera colonies. A second experiment with a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…Liu et al (2010b) also used DGGE to compare the microbial communities of co-existing flocs and granules treating wastewater and reported similar results, which led them to speculate that microbial selection between flocs and granules during steady state is not strong. While it has been demonstrated that the microbial community within a single reactor shifts over time as granules are developed (Williams and de los Reyes 2006), our results indicate that the dominant bacterial community composition of granules and flocs, at some 'steady-state' (in this case, after over 2 years) is similar. This highlights the importance of granule physical structure to developing and maintaining higher reaction rates compared to flocs.…”
Section: Potential Granule Contribution To Nitrification and Denitrifcontrasting
confidence: 45%
“…Liu et al (2010b) also used DGGE to compare the microbial communities of co-existing flocs and granules treating wastewater and reported similar results, which led them to speculate that microbial selection between flocs and granules during steady state is not strong. While it has been demonstrated that the microbial community within a single reactor shifts over time as granules are developed (Williams and de los Reyes 2006), our results indicate that the dominant bacterial community composition of granules and flocs, at some 'steady-state' (in this case, after over 2 years) is similar. This highlights the importance of granule physical structure to developing and maintaining higher reaction rates compared to flocs.…”
Section: Potential Granule Contribution To Nitrification and Denitrifcontrasting
confidence: 45%
“…Only a small number of published papers have used molecular methods to study fungi in wastewater treatment plant communities, and these have focused on fungi associated with aerobic granules [70,72]. Several of the 18S rRNA sequences recovered from plants A and B were closely related to the fungal sequences reported by Weber et al [70].…”
Section: Discussionmentioning
confidence: 92%
“…Clones A63 (plant A), B34 (plant B), C79 (plant C), D45 (plant D) and E46 (plant E) also clustered with the Cercozoan (infrakingdom Rhizaria). Partial Cercozoa sequences have been recovered from aerobic granules from an SBR treating synthetic wastewater [72]. …”
Section: Non-fungal 18s Rrna Sequences In Treatment Plant Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new kind of bioreactor was developed for the cultivation of aerobic granules (Williams and de los Reyes 2006). This annular gap bioreactor (also called a Couette-Taylor bioreactor; CTB) provides shear by placing the biomass between two rotating, concentric cylinders.…”
Section: Introductionmentioning
confidence: 99%